National Parks and rural development : (Island Press, 2000)
The editors also provide a detailed conclusion which summarizes policy implications and presents specific recommendations for improving rural development and park management policies.It will be an important work for agency personnel, nongovernmental organizations, and students and scholars of rural economic development, public policy, environmental economics, and related fields.